Structural Behavior of Reinforced Concrete One-Way Slabs Cast with Self-Compacting Concrete Containing Recycled Concrete as Coarse Aggregate - Altaee, Malik K. Eb.; Khudair, Jamal A. Samad (Basrah Journal for Engineering Sciences, 2020)
This work deals with the effect of using Recycled Concrete Aggregate (RCA) as a partial replacement of coarse aggregate in Self-Compacting Concrete (SCC), on the structural behavior (flexure and shear) of reinforced concrete one-way slabs. To the authors’ knowledge, this study is one of limited studies concerning the behavior of recycled aggregate concrete one-way slabs subjected to line loading with significant replacement of conventional aggregates by recycled concrete aggregate (up to 75 %). Three replacement ratios were considered: 25 %, 50 %, and 75 %. The mixes (with natural stone coarse aggregate, NCA) have an averaged compressive strength of ($F_{cu} = 42 \text{ MPa}$) at the age of 28 days with a tolerance of ($± 1.5 \text{ MPa}$). While, the mixes (with RCA) have an averaged compressive strength of ($38.5, 36.5, \text{ and } 34 \text{ MPa}$) for the three replacement ratios respectively, at the age of 28 days with a tolerance of ($± 2 \text{ MPa}$). All the slabs were cast with length of ($1600 \text{ mm}$), width of ($600 \text{ mm}$), while the thickness was variable. For this purpose, sixteen reinforced concrete one-way slabs were cast and divided into five groups (G1 to G5). Different parameters that affect the behavior of one-way slabs were studied and include type of failure, replacement ratios of NCA by RCA, amount of main reinforcement, thickness and locations of line loadings along the span. Hardened concrete specimens results show that the **compressive strength** $F_{cu}$, **tensile strength** $F_t$, **modulus of rupture** $F_r$, and **modulus of elasticity** $E$ were decreased as the RCA replacement increased. The experimental results of slabs show that the **ultimate capacity** of slabs decreased as the RCA replacement increased, the **deflection** and **strain** increase as the RCA replacement increases and the **crack width** increases as the RCA replacement increases. From the results of ultimate capacity, cracking load and moment, deflections, crack width and pattern and concrete surface strains, it can be concluded that the recycled concrete aggregate can be used as a partial replacement of natural coarse aggregate to produce self-compacting concrete mixes. Also, the behavior of one way slabs cast with SCC containing RCA is acceptable.